Secure scheme for user authentication and authorization in android environment - Dar, Humaira; Al-Khateeb, Wajdi Fawzi Mohammed; Habaebi, Mohamed Hadi (IJERA, 2013)
Providing ultimate security in sensitive transaction and communication of online premium application is still a question mark of standardization in the area of networking and security. It has been seen that currently majority of the authentication and authorization techniques are usually designed on the top of One Time Password on user trusted hand held device. However, due to various lethal threats on mobile security systems, it can be said that existing security is not sufficient. Keeping in viewpoint of security on effective authentication and authorization, this paper proposes a technique that exponentially minimizes the operational cost by using secure hash algorithms that has the potential to generate mobile-based One Time Passwords (OTPs) scheme on Android environment ensuring enhanced protection with respect to password security. Experimented on java platform, the implementation techniques discussed in the paper are found to be very robust